Effects of γCo-60 radiation on the growth and development of peppermint (Mentha arvensis L.) - Tran Thi , Le Minh; Nguyen , Truong Giang; Bui Thi , Hong Gam; Le , Quang Luan (Nuclear Science and Technology, 2015)
In this study, mints were regenerated from calluses irradiated by γ - rays (Co-60) at doses from 0 to 70 Gy. After 4 times of propagation, the M1V4 mints were transferred in a greenhouse for assessments of growth, development and essential oil content. Mint regenerated from calluses irradiated at low doses (0, 3, 4, 6, 8 and 10 Gy) showed no morphological difference compared to the control plants. However, low-dose irradiated mints showed better effect on growth and development, and mints regenerated from 6Gy-irradiated sample had essential oil content with 1.3 times higher than that of control group. In case of plants irradiated at higher dose (30, 40, 50, 60 and 70 Gy), there were morphological variations such as stem become bigger and color of stem become purple. Especially, samples irradiated at 60 Gy showed better in growth, development and essential oil content (1.34 times higher than the control plants) and these characters were stable in M1V4. Among the irradiated mints, purple stem variations had the highest essential oil yield with 1.7 times higher than that of the original plants.